2023
DOI: 10.3847/1538-4357/acb047
|View full text |Cite
|
Sign up to set email alerts
|

The Bimodal Absorption System Imaging Campaign (BASIC). I. A Dual Population of Low-metallicity Absorbers at z < 1

Abstract: The bimodal absorption system imaging campaign (BASIC) aims to characterize the galaxy environments of a sample of 36 H i-selected partial Lyman limit systems (pLLSs) and Lyman limit systems (LLSs) in 23 QSO fields at z ≲ 1. These pLLSs/LLSs provide a unique sample of absorbers with unbiased and well-constrained metallicities, allowing us to explore the origins of metal-rich and low-metallicity circumgalactic medium (CGM) at z < 1. Here we present Keck/KCWI and Very Large Telescope/MUSE observations of 11 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 174 publications
(277 reference statements)
0
11
0
Order By: Relevance
“…The references from which we collect these data, are also listed in the last column of the table. Virial radii of the galaxy-associations are reported in the literature for all three LLSs of our X-Ray-halo [3,8,19] , while the halo mass is reported only for the LSS along the sightline to PKS 0405-123 [3] . For the other two LSSs we derive Mh from Rvir, through the relationship 𝑀 ℎ = Finally, the last row of ED Table 2 lists the property of the X-ray-halo that we use in this work.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The references from which we collect these data, are also listed in the last column of the table. Virial radii of the galaxy-associations are reported in the literature for all three LLSs of our X-Ray-halo [3,8,19] , while the halo mass is reported only for the LSS along the sightline to PKS 0405-123 [3] . For the other two LSSs we derive Mh from Rvir, through the relationship 𝑀 ℎ = Finally, the last row of ED Table 2 lists the property of the X-ray-halo that we use in this work.…”
Section: Methodsmentioning
confidence: 99%
“…Properties of the LLS-galaxy associations and the X-ray-halo. The three LLSs that we use to build our X-Ray halo, and their galaxy associations, have been reported and discussed in several studies [3,6,8,[10][11][12][13]19] . ED Table 2 lists the properties of the LLS-galaxy associations relevant to this work: namely the stellar-mass M* (when available), halo mass Mh (defined as M200, i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three LLSs that we use to build our X-ray halo and their galaxy associations have been reported and discussed in several studies (Fox et al 2013;Lehner et al 2013;Stocke et al 2013;Werk et al 2013;Keeney et al 2017;Burchett et al 2019;Wotta et al 2019;Berg et al 2023), and their properties are reported in Table 5 of Appendix B. They all have H I column densities close to the lowest threshold, N H I = 10 16.2 cm −2 , of the LLS definition in Lehner et al (2013) and are seen at impact parameters (i.e., the line of sight to the galaxy center projected distance) of ρ > 90 kpc (Table 5 in Appendix B).…”
Section: Sample Selection and The X-ray Halomentioning
confidence: 99%
“…Such large volumes of space surrounding the stellar disks are not empty but are known to host clouds of cool (T ; 10 4 K) gas gravitationally bound to the galaxy. As suggested by the extensive studies carried out for the local Universe in the farultraviolet (FUV) band (∼900-2000 Å) with the Hubble Cosmic Origin Spectrograph (COS; McPhate et al 2000), this cool circumgalactic matter (cool CGM) may be in photoionization equilibrium with the external metagalactic UV radiation field in which it is embedded (e.g., Fox et al 2013;Lehner et al 2013Lehner et al , 2018Lehner et al , 2019Stocke et al 2013;Werk et al 2013Werk et al , 2014Keeney et al 2017;Berg et al 2019Berg et al , 2023Wotta et al 2019, but see also Bregman et al 2018 and references therein for alternative possibilities) and often coexists with higher-ionization gas in a different physical state probed by Li-like ions of oxygen (e.g., Prochaska et al 2011;Stocke et al 2013;Prochaska et al 2019;Tchernyshyov et al 2022) and/or neon (e.g., Burchett et al 2019). Under the pure photoionization equilibrium hypothesis, the cool CGM may contribute importantly to the galaxy baryon budget; for typical L * galaxies 12 with a halo mass of 1.6 × 10 12 M e and a factor of 4 deficit of baryons (e.g., McGaugh et al 2010), it may account for up to 50% of the missing baryonic matter (Werk et al 2014; but see also Bregman et al 2018).…”
Section: Introductionmentioning
confidence: 99%